2006
DOI: 10.1111/j.1752-0606.2006.tb01597.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing Emotion: The Use of Therapeutic Storytelling

Abstract: Even though using metaphors in a therapeutic context is common, there are very few studies that address their effects. This study examines the effects of storytelling in therapy. After discussing a problem in a current relationship, 42 female participants were randomly assigned to receive either a story or psychoeducational information. Results indicated that both treatments were equally successful in reducing amounts of negative affect and negative feelings toward the relationship. In addition, each story was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…Practitioners need to (a) incorporate the beliefs and values, including the families' understanding and use of spirituality, in the session to build and maintain their trust and to shape the therapy process; (b) listen intentionally to families and display curiosity about their strengths, including their sense of resilience; and (c) listen also for and integrate the families' use of stories or storytelling in their therapeutic journey toward finding successful outcomes. The use of these strategies fits well with such approaches of therapy as narrative, solution focused, and multisystems (Boyd-Franklin, 2003;Parker & Wampler, 2006;Perkins-Dock, 2005).…”
Section: Discussionmentioning
confidence: 79%
“…Practitioners need to (a) incorporate the beliefs and values, including the families' understanding and use of spirituality, in the session to build and maintain their trust and to shape the therapy process; (b) listen intentionally to families and display curiosity about their strengths, including their sense of resilience; and (c) listen also for and integrate the families' use of stories or storytelling in their therapeutic journey toward finding successful outcomes. The use of these strategies fits well with such approaches of therapy as narrative, solution focused, and multisystems (Boyd-Franklin, 2003;Parker & Wampler, 2006;Perkins-Dock, 2005).…”
Section: Discussionmentioning
confidence: 79%
“…The use of anecdotes and stories within some forms of psychoanalytical and Ericksonian therapies are examples of such incidences (e.g., Parker & Wampler, 2006). However, in the frameworks adopted by Kopp (1995), Lawley and Tompkins (2000) and Sims (2003), the practitioner's role is primarily to aid the client in the exploration and transformation of their own (e.g., "client generated") metaphor.…”
Section: Discussionmentioning
confidence: 99%
“…Counselling psychology studies have demonstrated that good therapeutic outcomes are attributed to the use of metaphor by counsellors (McMullen, 1989;Levitt, Korman, & Angus, 2000) and that the use of therapist-introduced metaphor is as effective as a psycho-educational approach (Parker & Wampler, 2006;Powell, Newgent, & Lee, 2006). Furthermore, metaphors are useful for exploring cultural differences and promoting multicultural understanding (Abernethy, 2002).…”
Section: Applying Research On Metaphor To Adventure Therapymentioning
confidence: 96%